Analysis of Character Education in Curriculum 13 to Build Moral Awareness in Education at SMA Muhammadiyah 2 Sidoarjo - Guntur Suprianto; Nurdyansyah Nurdyansyah; Nyong ETIS (International Consortium of Education and Culture Research Studies, 2020)
Character education in the 2013 curriculum aims to improve the quality of the process and educational outcomes that lead to the formation of character and noble character of students in full, integrated, and balanced in accordance with the standard competence of graduates in each educational unit. Forming good character is the primary obligation of an educator. Based on the description above, researchers conducted an analysis of character education in the 2013 curriculum to shape the moral awareness of education in schools through qualitative research. From the interviews conducted, the results obtained from the character values ​​embedded in the school are honesty.